PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN PT POS INDONESIA (PERSERO) KANTOR POS SEMARANG) - Ardien Ardiansyah; Dinalestari Purbawati (Jurnal Ilmu Administrasi Bisnis, 2020)
So intense business competition in the modern era, companies must pay attention to the quality of its human resources. Because human resources are the most important in running a company. this is because employees can act as thinkers, planners in company activities that require the company to achieve the desired goals. In this company expects a high increase in the company to encourage the progress of the company. but in reality the performance of employees at PT Pos Indonesia (Persero) Kantor Pos Semarang is still relatively low, as evidenced by the problem of lack of discipline in work, mistakes in work so that it is less effective and efficient at work and problems that are less supportive. This of course is a challenge for the company because it will hamper the achievement of company goals. This research aims to study work competence and the physical work environment on the performance of the employees of PT Pos Indonesia (Persero) Kantor Pos Semarang. The type of research used is explanatory research, the sampling technique of this study used a saturated sample technique of 70 respondents. The technique of collecting data uses a questionnaire with a Likert measurement scale. The data analysis method used is regression analysis with the help of the SPSS program version 25.0. Based on the results of the analysis it can be concluded as a substitute for work and physical work environment on the performance of the employees of PT Pos Indonesia (Persero) Kantor Pos Semarang proven to be a simple work regression test to tell positive 0.208, The physical work environment is 0.223. Have t countc> t table for work discipline of 2,190, and physical work environment of 2,613 through multiple linear regression tests of work discipline and work environment have beta coefficient values of 0.236 and 0.245. The advice given to the company is to improve in terms of reinforcing existing regulations in the company and improving the work environment in the PT Pos Indonesia (Persero) Kantor Pos Semarang.